Special balance exercises and their positive influence for sport performance - Psalman, V. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Many sports require different and special preparation with the aim to develop all needed abilities and skills. That is why coaches apply some special means and exercises in training praxis. Achieving excellent performance is possible only in case of extreme and sufficient development of balance abilities because movement in any sport is realized mostly in unstable conditions. Aim: The aim of this study was to get a deeper insight view on balance ability training and offer some special balance exercises for more effective sport preparation and training process. Methods: Twenty six athletes in tennis and sailing were observed during their sport preparation and during their main sport season. The first group was created from 13 athletes - experimental group and had preparation with using a special balance means and exercises twice a week, the second - control group had also 13 athletes which trained in a normal way. All tennis players and sailors are members of top sport clubs in Slovakia in age from 15 to 18 years. The standardized test of static balance on stabilographic board was used. The task of tested person was to keep static balance in standing position during 40 seconds. The accuracy was established on circle with 1 mm diameter. Time recorded in percents valuated the level of static balance. Sport performances were evaluated by three coaches and achieved sport results were taken into the consideration as well. Results: During the observed period - one sport season, athletes from the first group started to be well balanced in any position in different sport situations. This leads to improvemen mainly their techniques and personal performances. Difference in sport performance was confirmed by achieved better national ranking (up to 22 percent). Following special means and exercises were realized during the sport season with experimental group of athletes in fitness preparation: 1.Sitting and balancing on the fitball. 2.Sitting, balancing on the fitball and throwing another fitball. 3.Standing on knees and balancing on the fitball. 4.Standing on knees and balancing on the fitball and throwing another fitball. 5.Standing on knees and balancing on the fitball, throwing another fitball over the net and playing game (fitball tenis). 6.Standing and balancing on the fitball. 7.Standing and balancing on the fitball and throwing another fitball. 8.Monocycle free riding 9.Monocycle slalom riding Conclusions: Special balance exercises in training preparation are helpful for achieving better sport results. Exercises have also consistent beneficial effect on mood and psychological well-being, anxiety, depression, and psychological stress and may enhance cognitive functioning.